Trypanosomiasis causing mortality outbreak in Nile tilapia intensive farming: Identification and pathological evaluation - Jesus, Raphael Barbetta de [UNESP]; Gallani, Sílvia Umeda [UNESP]; Valladão, Gustavo Moraes Ramos [UNESP]; Pala, Gabriela [UNESP]; Silva, Thiago Fernandes Alves da [UNESP]; Costa, Jaqueline Custódio da [UNESP]; Kotzent, Suzana [UNESP]; Pilarski, Fabiana [UNESP] (Elsevier, 2018)
Trypanosomes are flagellated parasite protozoans that prey especially on wild fish and have recently been described affecting fish in aquaculture. The present study was carried out during a mortality outbreak of Nile tilapia Oreochromis niloticus reared in net cages. Samples of 10 fish in the finishing phase showing unspecific signs, such as anorexia, skin darkening and gill paleness, were analyzed using hemogram, parasitology, microbiology, histopathology, electron microscopy and molecular identification. For microbiological analysis, the kidney was collected aseptically and cultured on tryptone soy agar for 48 h at 30 °C. For parasitological analysis, skin, gills, intestinal contents and blood scrapings were examined. Photomicrographs of the parasite were measured. For molecular identification, blood samples were processed and sequenced for amplification of the 18S rDNA gene. Gills, liver, spleen, kidney, heart and intestine were sampled for histopathological processing. The microbiological results indicated that the fish were not infected with bacteria. Scrapings of the skin and gills revealed the massive presence of kinetoplastids, which were also observed in greater numbers than erythrocytes in the blood. Intestines were not affected by endoparasites. The morphometric characteristics indicated the presence of the Trypanosoma genus, which was confirmed in the sequenced samples, where 95% and 98% of the identity were Trypanosoma sp. In histopathology, all organs presented different levels of alteration, accompanied by large numbers of the parasite in small and large vessels. The main findings were the description of mast cell infiltrates in the gill and intestine, as well as multifocal aggregates of melanomacrophages in the liver, pancreas, spleen and kidney. Furthermore, the study addresses the newest features of clinical signs of infected fish and possible causes of infestations and compares the diagnosis of this hemoparasite with other hemoflagellates. To our knowledge, this study represents the first outbreak of Trypanosoma in Nile tilapia in South America. The authors warn of possible new cases of trypanosomiasis in aquaculture, recommending possible forms of containment and biosecurity measures.
Keywords: Hemoparasite; Histopathology; Nile tilapia; Parasitosis; PCR; Trypanosoma